ChemInform Abstract: Lewis Acid Catalyzed Cascade Reaction of 3‐(2‐Benzenesulfonamide)propargylic Alcohols to Spiro[indene‐benzosultam]s. Issue 23 (June 2015) - Sun, Lang; Zhu, Yuanxun; Wang, Jing; Lu, Ping; Wang, Yanguang
Abstract The reaction comprises a cascade process which allows trapping with NIS or NBS in order to obtain halogenated spiro[indene‐benzosultam]s which are further arylated via Suzuki‐coupling reactions.